Modification of Cold-Sprayed Aluminum Coating on Nickel-Aluminum Bronze by Micro-Arc Oxidation - Yürektürk, Yakup (Springer, 2021)
This study aims to improve the wear resistance of nickel-aluminum bronze (NAB) substrates by micro-arc oxidation (MAO). As this treatment is difficult to apply to NAB surface, cold spraying (CS) was first used to deposit aluminum with a purity of 99.5% onto the NAB substrates. The aluminum-coated substrate was then treated by MAO to convert the aluminum layer into Al2O3 coating in order to enhance the wear resistance. The tribological behavior of NAB substrates with or without the alumina coating was evaluated with a dry sliding wear test using a ball-on-flat reciprocating tester with varied testing loads ranging from 1 to 5 N. The results demonstrated that the oxide layer (Al2O3) formed on the aluminum layer enhanced the wear resistance of NAB alloy against 100Cr6 steel ball. Compared to uncoated NAB alloy, the wear resistance (inverse of wear rate) of the NAB alloy with the MAO coating was at least nine times higher than that of the uncoated NAB alloy at all testing loads.
Keywords: cold spraying; micro-arc oxidation; Wear; nickel-aluminum bronze alloy